Anode plate and secondary battery
Patent Information
- Application Number
- JP2023127210
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
AI Technical Summary
【0014】 本発明によれば、効率よく合材層の剥離を抑制することができる。
Smart Images

Figure 2025022533000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode plate and a secondary battery. [Background technology]
[0002] For example, some electrode plates for secondary batteries, such as lithium ion secondary batteries, are formed by applying an electrode mixture to a substrate that serves as a current collector. That is, a binder, a thickener, and the like are added to the electrode mixture along with the electrode active material. For example, carboxymethyl cellulose is contained as a thickener in the negative electrode mixture. Furthermore, such electrode plates for secondary batteries often have a mixture-coated portion in which the electrode mixture applied to the substrate forms a mixture layer, and an uncoated portion in which the electrode mixture is not applied to the substrate. In addition, it is common to use the uncoated portion as a terminal connection portion.
[0003] In addition, in such a secondary battery electrode plate, it is an important issue that the composite layer coated on the substrate is difficult to peel off, that is, to increase the peel strength of the composite layer. In light of this point, for example, Patent Document 1 discloses a configuration in which a powdered thickener is mixed in a powder mixing step prior to the kneading step in which the raw materials of the electrode composite are kneaded, and a liquid thickener dissolved in water is mixed in a thickener aqueous solution mixing step subsequent to the kneading step. In this way, by mixing the thickeners in different states twice, it is possible to increase the peel strength of the composite layer without causing a decrease in battery performance as seen when the amount of the binder, which is a non-battery reaction component, is increased. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-93240 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in applications requiring high levels of battery performance, such as electric vehicles, further improvements in performance are being sought on a daily basis, and therefore further improvements are being sought in the above-mentioned conventional technologies in order to meet the evolving requirements. [Means for solving the problem]
[0006] Various aspects of the negative electrode plate and secondary battery that solve the above problems will be described below. Aspect 1 is a negative electrode plate comprising a composite-coated portion in which a negative electrode composite coated on a substrate forms a composite layer, and an uncoated portion on which the negative electrode composite is not coated, wherein the negative electrode composite contains carboxymethyl cellulose as well as a negative electrode active material, and the composite layer contains more undissolved particles of carboxymethyl cellulose at an end position of the composite-coated portion located at the boundary with the uncoated portion than at an inner position of the composite-coated portion separated from the uncoated portion relative to the end position.
[0007] According to the above configuration, when the composite layer is dried, the undissolved particles of carboxymethyl cellulose (CMC) contained in the composite layer inhibit the upward movement of the binder that occurs in the composite layer as the solvent evaporates. In other words, migration can be suppressed. This can increase the peel strength of the composite layer coated on the substrate. In particular, the peel strength can be effectively increased by distributing more undissolved particles of CMC contained in the composite layer toward the end positions of the composite coating portion where the peel strength of the composite layer is likely to decrease. This can efficiently suppress the peeling of the composite layer without causing a decrease in battery performance due to an increase in the amount of binder or CMC added to the electrode composite.
[0008] Aspect 2 is a negative electrode plate according to aspect 1, in which the grain area ratio of the undissolved particles in the microscopic image obtained by binarizing the microscopic image of the composite layer is greater at the end position of the composite coated portion than at the inner position of the composite coated portion.
[0009] According to the above-mentioned configuration, the content of undissolved CMC particles contained in the composite layer can be easily and accurately compared with a simple configuration, and thus, a negative electrode plate capable of efficiently suppressing peeling of the composite layer can be formed.
[0010] Aspect 3 is a negative electrode plate according to aspect 2, in which the grain area index is a value obtained by indexing the grain area ratio at the end position of the composite coating portion based on the grain area ratio at the inner position of the composite coating portion, and the grain area index is 150 or more.
[0011] According to the above-mentioned configuration, peeling of the composite layer can be efficiently suppressed. Aspect 4 is the negative electrode plate according to any one of Aspects 1 to 3, in which the content of the carboxymethyl cellulose in the negative electrode mixture is 0.1 wt % or more and 1.0 wt % or less.
[0012] According to the above-mentioned configuration, undissolved CMC particles are present in the composite layer, and the peel strength can be efficiently increased in a state where the undissolved particles are unevenly distributed at the edge positions of the composite coating portion.
[0013] A fifth aspect is a secondary battery including a negative electrode plate according to any one of the first to fourth aspects. Effect of the Invention
[0014] According to the present invention, peeling of the composite layer can be efficiently suppressed. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a perspective view of a secondary battery. [Diagram 2] FIG. 2 is an exploded view of the electrode assembly. [Diagram 3] FIG. 3 is a side view of the secondary battery. [Figure 4] FIG. 4 is a cross-sectional view of an electrode sheet showing the end positions of an uncoated portion and a composite-coated portion. [Diagram 5]FIG. 5 is a diagram illustrating the action of an electrode mixture containing undissolved particles of carboxymethyl cellulose (CMC). [Figure 6] FIG. 6 is a graph comparing the ease with which migration progresses for binders contained in a mixture layer when the mixture layer is dried. [Figure 7] FIG. 7 is a schematic diagram showing a cross-sectional image of a composite layer taken by a scanning electron microscope (SEM). [Figure 8] FIG. 8 is a plan view of the electrode sheet before cutting. [Figure 9] FIG. 9 is a graph comparing the contents of undissolved CMC particles contained in an electrode mixture layer. [Figure 10] FIG. 10 is a flowchart showing a method for calculating a particle area ratio that indicates the content of undissolved CMC particles contained in an electrode mixture layer. [Figure 11] FIG. 11 is a graph comparing the peel strength of composite layers. [Figure 12] FIG. 12 is a graph showing the results of measuring the peel strength of the electrode mixture layer of a negative electrode plate of a reference example that does not contain undissolved CMC particles in the electrode mixture layer. [Figure 13] FIG. 13 is a graph showing the results of measuring the peel strength of the electrode mixture layer for negative electrode plates according to examples in which undissolved CMC particles are contained in the electrode mixture layer. [Figure 14] FIG. 14 is a perspective view of a comma coater. [Figure 15] FIG. 15 is a cross-sectional view of a comma coater. [Figure 16] FIG. 16 is a top view of the comma coater. [Figure 17] FIG. 17 is a table showing the test results of the secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of a secondary battery will be described with reference to the drawings. (Lithium-ion secondary battery) 1, the secondary battery 1 includes an electrode assembly 10 in which a positive electrode 3, a negative electrode 4, and a separator 5 are integrated, and a case 20 that houses the electrode assembly 10. The secondary battery 1 of this embodiment has a configuration as a lithium ion secondary battery in which the electrode assembly 10 in the case 20 is impregnated with a non-aqueous electrolyte solution (not shown).
[0017] More specifically, in the secondary battery 1 of this embodiment, the positive electrode 3, the negative electrode 4, and the separator 5 are laminated with a sheet-like outer shape. Then, by winding up the laminate of the positive electrode 3, the negative electrode 4, and the separator 5, an electrode body 10 is formed in which the positive and negative electrodes and the separators 5 are alternately arranged in the radial direction with the separator 5 sandwiched between the positive electrode 3 and the negative electrode 4.
[0018] The case 20 of this embodiment includes a case body 21 having a flat, substantially rectangular box shape, and a lid member 22 that closes an open end 21x of the case body 21. The electrode body 10 of this embodiment has a flat outer shape that corresponds to the box shape of the case 20.
[0019] (Electrode sheet and electrode body) More specifically, as shown in FIG. 2, in the secondary battery 1 of this embodiment, the positive electrode 3 and the negative electrode 4 each have a configuration as an electrode sheet 35 including a current collector 31 having a sheet-like outer shape and an electrode active material layer 32 laminated on this current collector 31.
[0020] Specifically, for the electrode sheet 35P for the positive electrode 3, an electrode mixture containing lithium transition metal oxide as a positive electrode active material, i.e., a composite paste 37P as a positive electrode mixture, is applied to a substrate 36P made of aluminum or the like that constitutes the positive electrode current collector 31P. For the electrode sheet 35N for the negative electrode 4, an electrode mixture in the form of a slurry containing a carbon-based material that serves as a negative electrode active material, i.e., a composite paste 37N as a negative electrode mixture, is applied to a substrate 36N made of copper or the like that constitutes the negative electrode current collector 31N. Furthermore, each of these composite pastes 37P and 37N contains a binder. In the secondary battery 1 of this embodiment, the composite pastes 37P and 37N are dried to form the corresponding positive electrode active material layer 32P and negative electrode active material layer 32N on the positive and negative electrode sheets 35P and 35N, respectively.
[0021] Furthermore, in the secondary battery 1 of this embodiment, the positive and negative electrode sheets 35P, 35N are each shaped into a belt-like shape. The electrode body 10 of this embodiment has a configuration as a wound body in which the positive and negative electrode sheets 35P, 35N, which are stacked with the separator 5 sandwiched therebetween, are wound around a winding axis 10x extending in the width direction of the belt-like shape (the left-right direction in FIG. 2).
[0022] 2, the separator 5 and each electrode sheet 35 are wound in such a manner that the electrode sheet 35P constituting the positive electrode 3 is wound inward. However, this figure is one example showing the structure of the electrode body 10, and the separator 5 and each electrode sheet 35 may be wound in such a manner that the electrode sheet 35N constituting the negative electrode 4 is wound inward. This determines whether the electrode sheet 35 arranged on the outermost shell of the electrode body 10 is the electrode sheet 35P constituting the positive electrode 3 or the electrode sheet 35N constituting the negative electrode 4.
[0023] 1 to 3, the cover member 22 of the case 20 is provided with a positive electrode terminal 38P and a negative electrode terminal 38N that protrude to the outside of the case 20. Furthermore, each electrode sheet 35 has an uncoated portion 39 in which the electrode active material layer 32 is not formed on the current collector 31. The secondary battery 1 of this embodiment is configured such that, by utilizing these uncoated portions 39, the electrode sheet 35P constituting the positive electrode 3 and the positive electrode terminal 38P are electrically connected, and the electrode sheet 35N constituting the negative electrode 4 and the negative electrode terminal 38N are electrically connected.
[0024] Specifically, the electrode body 10 of this embodiment is housed in the case 20 with its winding axis 10x aligned along the longitudinal direction (left-right direction in FIG. 1) of the cover member 22, which is an elongated, generally rectangular plate. Furthermore, in this state, an uncoated portion 39P of an electrode sheet 35P constituting the positive electrode 3 is connected to a positive electrode terminal 38P via a connecting member 40P. Similarly, an uncoated portion 39N of an electrode sheet 35N constituting the negative electrode 4 is connected to a negative electrode terminal 38N via a connecting member 40N.
[0025] Furthermore, an electrolyte solution 45 is injected into the case 20. That is, the electrolyte solution 45 of the secondary battery 1 having a configuration as a lithium ion secondary battery is one in which a lithium salt serving as a supporting salt is dissolved in an organic solvent. Thus, the secondary battery 1 of this embodiment is configured such that the electrode body 10 sealed in the case 20 is impregnated with the electrolyte solution 45.
[0026] (End position of composite coating part and peel strength of composite layer) As shown in FIG. 2 and FIG. 4, in the secondary battery 1 of this embodiment, each electrode sheet 35 constituting the positive and negative electrode plates 50 has an uncoated portion 39 where the composite paste 37 is not coated on the substrate 36 that is the current collector 31, as described above. In the electrode sheet 35 of this embodiment, the uncoated portion 39 is provided at the width direction end (left end in FIG. 4) 35e of the electrode sheet 35 having a belt-shaped outer shape. In other words, the electrode sheet 35 of this embodiment has a composite coating portion 51 where the composite paste 37 is coated on the substrate 36 at a position that is on the inside in the width direction (right side in FIG. 4) of the uncoated portion 39. That is, in the electrode sheet 35 of this embodiment, the composite paste 37 coated on the substrate 36 forms a composite layer 52 containing an electrode active material in the composite coating portion 51. In the electrode sheet 35 of this embodiment, the composite layer 52 formed in the composite coating portion 51 functions as the electrode active material layer 32.
[0027] 4, in the electrode sheet 35 of this embodiment, an end position Xe of the composite-coated portion 51 in the width direction is the boundary between the composite-coated portion 51 and the uncoated portion 39. That is, an edge portion 52e of the composite layer 52 laminated on the substrate 36 is disposed at the end position Xe of the composite-coated portion 51. In the secondary battery 1 of this embodiment, the composite paste 37 applied to the substrate 36, specifically, the composite paste 37N as the negative electrode composite, is adjusted so that the composite layer 52 is less likely to peel off at the end position Xe of the composite-coated portion 51.
[0028] That is, at the end position Xe of the composite coating portion 51 located at the boundary with the uncoated portion 39, the composite paste 37 applied to the substrate 36 is likely to flow. For this reason, a thin portion 54 whose thickness d is gradually reduced in the width direction of the electrode sheet 35 toward the uncoated portion 39 side (left side in FIG. 4) tends to be formed at the edge portion 52e of the composite layer 52. The thin portion 54 is formed at the edge portion 52e of the composite layer 52 in the width direction of the electrode sheet 35, for example, in a range of about 200 μm. Furthermore, in the portion where the composite layer 52 is thinned in this way, the composite paste 37 dries quickly, and unevenness tends to occur in the distribution of the binder contained in the composite paste 37, that is, the distribution of the binder in the composite layer 52 after drying. Specifically, when the mixture layer 52 formed on the substrate 36 dries and the solvent evaporates from the surface 52s of the mixture layer 52, the binder is likely to move upward together with the solvent. In other words, migration is likely to occur. As a result, a problem occurs in that the peel strength of the mixture layer 52 is likely to decrease at the end position Xe of the mixture-coated portion 51. The term "peel strength" can be rephrased as "peel resistance strength" or "binding strength", etc.
[0029] (undissolved particles of carboxymethylcellulose) In consideration of this, in the secondary battery 1 of this embodiment, as shown in Fig. 5, for an electrode sheet 35N that becomes a negative electrode plate 50N, a composite paste 37N that is applied to a base material 36N thereof contains undissolved particle components. Thus, the secondary battery 1 of this embodiment is configured to suppress the occurrence of the above-mentioned migration.
[0030] More specifically, in the secondary battery 1 of this embodiment, the composite paste 37N on the negative electrode 4 side contains carboxymethyl cellulose (CMC) that functions as a thickening agent. In the secondary battery 1 of this embodiment, the CMC exists in the composite paste 37N in a state where a part of it remains undissolved, that is, in the form of undissolved particles 60. Furthermore, in the secondary battery 1 of this embodiment, the undissolved particles 60 of the CMC inhibit the upward movement of the binder 62 that occurs in the composite layer 52N as the solvent 61 evaporates when the composite layer 52N is dried. Thus, the secondary battery 1 of this embodiment is configured to keep more of the binder 62 contained in the composite layer 52 near the surface 36s of the base material 36N, thereby increasing the peel strength of the composite layer 52N.
[0031] In the secondary battery 1 of this embodiment, for example, styrene butadiene latex (SBR) or the like is used as the binder 62 for the negative electrode 4. As the CMC added to the composite paste 37N that becomes the negative electrode composite material, a sodium salt (CMC-Na) or a lithium salt (CMC-Li) is used.
[0032] Specifically, as shown in Fig. 6, the amount of migration in the composite layer 52N that does not contain undissolved CMC particles 60 is set to "100", and the value that indexes the ease with which the migration progresses is set to the "migration index". In this case, the secondary battery 1 of this embodiment that contains undissolved CMC particles 60 in the composite layer 52N has a "migration index" lower than "100". From the value of this "migration index", the migration suppression effect due to the presence of undissolved CMC particles 60 in the composite layer 52N can be confirmed.
[0033] As shown in Fig. 7, the "amount of migration" of the binder 62 in the composite layer 52N is measured by observing the cross section of the composite layer 52N using a scanning electron microscope (SEM). Furthermore, when the cross section of the composite layer 52N is divided into three regions, an upper region δ1, a middle region δ2, and a lower region δ3, the area occupied by the binder 62 (not shown) in each of these regions in the analysis image is measured. Then, for the area occupied by the binder 62, the ratio of the value of the upper region δ1 to the value of the middle region δ2 is used as the value representing the "amount of migration".
[0034] (Uneven distribution of CMC undissolved particles at the edges) 8, an end position Xe of the composite-coated portion 51N located at the boundary with the uncoated portion 39N is compared with an inner position Xi of the composite-coated portion 51N that is farther away from the uncoated portion 39N than the end position Xe. In this case, the secondary battery 1 of this embodiment is configured such that the end position Xe contains more undissolved CMC particles 60 in the composite layer 52N than the inner position Xi.
[0035] Specifically, in the secondary battery 1 of this embodiment, the composite paste 37N is applied in a state in which uncoated portions 39N, 39N are formed at both widthwise ends (vertical ends in FIG. 8) of a base material 36N having a foil shape extending in a strip shape. Furthermore, the electrode sheet 35X thus formed is cut into a slit 70 at its widthwise central position. The secondary battery 1 of this embodiment is configured so that each of the two divided electrode sheets 35N, 35N is used for its negative electrode plate 50N.
[0036] That is, in the secondary battery 1 of this embodiment, the two positions adjacent to the uncoated parts 39N, 39N formed at both ends in the width direction of the electrode sheet 35X before cutting are the end positions Xe, Xe of the composite coated part 51N. In the secondary battery 1 of this embodiment, the end positions Xe, Xe of the composite coated part 51N are set in a width direction range in which the composite layer 52N coated on the base material 36N is easily peeled off, for example, a position range about 8 mm inside in the width direction from the uncoated parts 39N, 39N. In the secondary battery 1 of this embodiment, the position range between the end positions Xe, Xe in the width direction of the electrode sheet 35X is the inner position Xi of the composite coated part 51N.
[0037] Furthermore, as shown in Figures 8 and 9, in the secondary battery 1 of this embodiment, the undissolved CMC particles 60 contained in the composite layer 52N are concentrated in the end position Xe rather than in the inner position Xi of the composite coating portion 51N.
[0038] In detail, as shown in FIG. 10, in the secondary battery 1 of this embodiment, a microscope image Vd is obtained by using an optical microscope for the surface 52s of the composite layer 52N applied to the base material 36N (step 101). Next, the microscope image Vd is binarized by image analysis (step 102). Note that, by this binarization process, for example, the undissolved CMC particles 60 shown in the microscope image Vd are displayed as "black" and the parts other than the undissolved particles 60 are displayed as "white". Furthermore, the area of the undissolved CMC particles 60 shown in the binarized microscope image Vd is measured as a "particle area" (step 103). Then, by dividing this "particle area" by the "region area" of the entire microscope image Vd, a "particle area ratio" of the undissolved CMC particles 60 in the microscope image Vd is calculated (step 104).
[0039] In the secondary battery 1 of this embodiment, the "particle area ratio" of the undissolved CMC particles 60 contained in the composite layer 52N is calculated for each of the end position Xe and the inner position Xi of the composite-coated portion 51N. Furthermore, the particle area ratio at the inner position Xi of the composite-coated portion 51N is set as a reference value of "100" and the particle area ratio at the end position Xe of the composite-coated portion 51N is indexed. In the secondary battery 1 of this embodiment, this value is used as the "particle area index" to evaluate the state in which the undissolved CMC particles 60 contained in the composite layer 52N are unevenly distributed more at the end position Xe than at the inner position Xi of the composite-coated portion 51N (see FIG. 9).
[0040] Specifically, as shown in FIG. 8, in the secondary battery 1 of this embodiment, for example, before the electrode sheet 35X is cut, the particle areas Se1 and Se2 of the undissolved particles 60 at the end positions Xe1 and Xe2 on both sides in the width direction of the composite coating section 51N are measured. Also, before the electrode sheet 35X is cut, for example, in the width direction center part of the composite coating section 51N, that is, near the set position of the slit 70, the particle area Si of the undissolved particles 60 at the inner position Xi is measured. Furthermore, the angle of view γ of the microscope image Vd used to measure these particle areas Se1, Se2, and Si, that is, the "area" of the entire microscope image Vd, is constant. In the secondary battery 1 of this embodiment, this makes it possible to calculate the particle area index Is of the undissolved particles 60 of the CMC contained in the composite layer 52N using the following formula.
[0041] Is=(Se1+Se2) / (Si×2) ···(1) For the sake of convenience, the shape and dimensions of the undissolved particle 60 and the angle of view γ of the microscope image Vd shown in FIG. 8 are described in a simplified manner. In addition, for the values of each particle area Se1, Se2, and Si in the above formula (1), it is preferable to use the average value obtained by performing measurements multiple times while changing the photographing position of the microscope image Vd. And, the above formula (1) is a formula obtained by common-dividing the value corresponding to the "area of the region" of the entire microscope image Vd included in the numerator and denominator, that is, the "denominator of the calculation formula for calculating the particle area ratio."
[0042] That is, as shown in Fig. 9, in the secondary battery 1 of this embodiment, the grain area index Is of the undissolved CMC particles 60 measured at the end position Xe of the composite-coated portion 51N is a value larger than "100". Specifically, in this example, the grain area index Is at the end position Xe is about 176. It is preferable that this grain area index Is is 150 or more. This makes it possible to confirm that the undissolved CMC particles 60 contained in the composite layer 52N are unevenly distributed more at the end position Xe than at the inner position Xi of the composite-coated portion 51N.
[0043] 11, in the secondary battery 1 of this embodiment, the peel strength of the composite layer 52N at the inner position Xi of the composite-coated portion 51N is set to "100," and the peel strength at the end position Xe of the composite-coated portion 51N is indexed. This value is then used as the "peel strength index" to evaluate the peel strength of the composite layer 52N at the end position Xe relative to the peel strength of the composite layer 52N at the inner position Xi of the composite-coated portion 51N, which serves as a reference.
[0044] 12 and 13, in the secondary battery 1 of this embodiment, for example, before the electrode sheet 35X is cut, the peel strength F of the composite layer 52N is measured for each width direction position. Furthermore, the average value of the measured peel strengths F is calculated for the end positions Xe1, Xe2 on both sides of the width direction position and the inner position Xi between the end positions Xe1, Xe2. Then, in the secondary battery 1 of this embodiment, these average values are respectively set as the peel strengths Fe1, Fe2 at the end positions Xe1, Xe2 and the peel strength Fi at the inner position Xi, and a peel strength index If is calculated by the following formula.
[0045] If=(Fe1+Fe2) / (Fi×2) ···(2) The peel strength F is measured by fixing the negative electrode plate 50N to a sample stand and gripping the composite layer 52N formed on the substrate 36N with a chuck or the like. The composite layer 52N is then peeled off from the substrate 36N using a tensile tester. At this time, the load is measured at each measurement position using an autograph or the like, and the strength of the force at which the composite layer 52N is peeled off from the substrate 36N is measured as the peel strength F of the composite layer 52N.
[0046] 12, in which the mixture layer 52N does not contain undissolved CMC particles 60, the occurrence of migration as described above is suppressed by optimizing the drying conditions, etc. This results in a configuration in which the peel strengths Fe1, Fe2 at the end positions Xe1, Xe2 are not significantly reduced from the peel strength Fi at the inner position Xi.
[0047] In contrast, in an embodiment in which undissolved CMC particles 60 contained in a composite layer 52N are unevenly distributed, with more at end positions Xe than at inner positions Xi of a composite-coated portion 51N, the peel strengths Fe1, Fe2 at end positions Xe1, Xe2 are higher than the peel strength Fi at inner position Xi. As shown in Fig. 11, the improved effect of the peel strengths Fe1, Fe2 at the end positions Xe1, Xe2 is reflected in the peel strength index If.
[0048] (How to prepare undissolved CMC particles) More specifically, in the secondary battery 1 of this embodiment, the undissolved CMC particles 60 contained in the composite paste 37N as the negative electrode composite material are adjusted by controlling the “degree of etherification of CMC” and the “mixture kneading state”, etc.
[0049] That is, CMC, which is a cellulose derivative, has three hydroxyl groups (-OH) in each glucose unit that is polymerized in a linear chain. The number of etherified hydroxyl groups among the three hydroxyl groups is the "degree of etherification."
[0050] In the secondary battery 1 of this embodiment, by using CMC with a relatively small value of the "degree of etherification", a part of the CMC added to the composite paste 37N remains undissolved. In other words, the composite paste 37N contains undissolved particles 60 of CMC.
[0051] In the secondary battery 1 of this embodiment, the rotation speed (RPM) of the kneading machine is kept relatively low when the composite paste 37N is kneaded, which makes it easier for a portion of the CMC that has been mixed in advance with the negative electrode active material to remain undissolved.
[0052] Furthermore, in the secondary battery 1 of this embodiment, the CMC content in the composite paste 37N is set to 0.1 wt% or more and 1.0 wt% or more. This allows the secondary battery 1 of this embodiment to efficiently increase the peel strength F in a state in which undissolved CMC particles 60 exist in the composite layer 52N and are unevenly distributed at the end position Xe of the composite coating portion 51N.
[0053] (Method of uneven distribution of undissolved CMC particles) As shown in Figs. 14 to 16, in the secondary battery 1 of this embodiment, a comma coater 80 is used to coat the composite paste 37N on the substrate 36N. That is, in the coating process of the composite paste 37N, the substrate 36N is continuously transported in a state where the foil shape extending in a strip shape is wound around a plurality of rolls 81. The comma coater 80 of this embodiment includes a comma roll 82 that has a spindle 82x parallel to the spindle 81x of a roll 81c called a "C roll" among the rolls 81 and is arranged in parallel with the roll 81c. Specifically, in the comma coater 80 of this embodiment, the comma roll 82 is arranged adjacent to the roll 81c at a position where the substrate 36N wound around the roll 81c is sandwiched from above. Furthermore, the roll 81c rotates counterclockwise in Fig. 15, and the comma roll 82 rotates clockwise in the same figure. The comma coater 80 of this embodiment is configured so that the substrate 36N, which is wound around the roll 81c from below, is continuously transported in such a manner that it is pulled out to the left side in Figure 15 through the gap between the roll 81c and the comma roll 82.
[0054] The comma coater 80 of this embodiment also includes a dam 85 that forms a storage section 83 for the composite paste 37N at a lateral position of the roll 81c (on the right side in Figs. 15 and 16). Furthermore, this dam 85 makes the surface 36s of the base material 36N wound around the roll 81c into a wall surface 83s of the storage section 83. That is, in the comma coater 80 of this embodiment, the composite paste 37N in the storage section 83 adheres to the surface 36s of the base material 36N that is transported in a state of being wound around the roll 81c. The comma coater 80 of this embodiment is configured to coat the composite paste 37N in such a manner that the comma roll 82 stretches the composite paste 37N that has adhered to the surface 36s of the base material 36N when the base material 36N is pulled out from the gap between the roll 81c and the comma roll 82.
[0055] As shown in Fig. 16, the comma coater 80 of this embodiment includes a composite supply unit 87 that supplies composite paste 37N to the storage unit 83 formed by the dam 85. In the comma coater 80 of this embodiment, the composite supply unit 87 has a cylindrical outer shape that discharges the composite paste 37N from its tip. Furthermore, the composite supply unit 87 is disposed at the center position in the width direction of the substrate 36N wound around the roll 81c. The comma coater 80 of this embodiment is configured such that the composite paste 37N is discharged from the composite supply unit 87 into the storage unit 83 toward the roll 81c side (left side in Fig. 16).
[0056] (action) That is, in the comma coater 80 of this embodiment, the composite material supply unit 87 discharges the composite material paste 37N into the storage unit 83, thereby forming a "flow" of the composite material paste 37N in the storage unit 83. Specifically, at the position where the composite material supply unit 87 is provided, that is, at the widthwise center position of the substrate 36N wound around the roll 81c, a "flow" of the composite material paste 37N toward the roll 81c is formed. Furthermore, the composite material paste 37N moving along the "flow" toward the roll 81c hits the substrate 36N constituting the wall surface 83s of the storage unit 83, thereby forming a "flow" from the widthwise center position of the substrate 36N toward the end along the axis of the roll 81c. Then, as the composite paste 37N moves along this "flow" toward the end portion and reaches the vicinity of both side walls 83x, 83x of the storage portion 83 formed by the dam 85, a gentle, spiral-shaped "flow" is formed in the composite paste 37N in the storage portion 83.
[0057] In the comma coater 80 of this embodiment, the "flow" of the composite paste 37N formed in the storage section 83 makes it easy for the undissolved CMC particles 60 contained in the composite paste 37N to remain near both side walls 83x, 83x of the storage section 83. That is, in the secondary battery 1 of this embodiment, the width direction range (up-down direction range in FIG. 16) of the storage section 83 along the axial direction of the roll 81c corresponds to the composite coated section 51N of the electrode sheet 35N that becomes the negative electrode plate 50N (see FIG. 8). Furthermore, the vicinity of both side walls 83x, 83x of the storage section 83, that is, both end positions in the width direction, correspond to the end positions Xe, Xe of the composite coated section 51N of the electrode sheet 35X before cutting. In this state, the secondary battery 1 of this embodiment is configured so that the composite paste 37N adhered to the surface 36s of the base material 36N forms a composite layer 52N, and the undissolved CMC particles 60 contained in this composite layer 52N are unevenly distributed at the end position Xe of the composite coating portion 51N.
[0058] Next, the effects of this embodiment will be described. (1) The electrode sheet 35N constituting the negative electrode plate 50N of the secondary battery 1 includes a composite-coated portion 51N in which a composite paste 37N as a negative electrode composite applied to a substrate 36N forms a composite layer 52N, and an uncoated portion 39N in which the composite paste 37N is not applied. The composite paste 37N further contains carboxymethyl cellulose (CMC) together with the negative electrode active material. The composite layer 52N contains more undissolved particles 60 of CMC at an end position Xe of the composite-coated portion 51N located at the boundary with the uncoated portion 39N than at an inner position Xi of the composite-coated portion 51N separated from the uncoated portion 39N than the end position Xe.
[0059] According to the above configuration, when the composite layer 52N is dried, the undissolved particles 60 of CMC contained in the composite layer 52N inhibit the upward movement of the binder 62 generated in the composite layer 52N due to the evaporation of the solvent 61. In other words, migration can be suppressed. This can increase the peel strength F of the composite layer 52N applied to the substrate 36N. In particular, the undissolved particles 60 of CMC contained in the composite layer 52 are unevenly distributed in greater amounts at the end positions Xe of the composite coating portion 51 where the peel strength F of the composite layer 52 is likely to decrease, thereby effectively increasing the peel strength F. This can efficiently suppress the peeling of the composite layer 52N without causing a decrease in battery performance due to an increase in the amount of the binder 62 or CMC added to the composite paste 37.
[0060] (2) A microscopic image Vd of the composite layer 52N is obtained, and the microscopic image Vd is binarized by image analysis. Furthermore, the "grain area ratio" of the undissolved particles 60 in the microscopic image Vd is calculated. In the negative electrode plate 50N, the "grain area ratio" of the undissolved particles 60 is larger at the end position Xe than at the inner position Xi of the composite coating portion 51N.
[0061] According to the above-mentioned configuration, the content of undissolved particles 60 of CMC contained in composite layer 52N can be easily and accurately compared with a simple configuration. As a result, negative electrode plate 50N capable of efficiently suppressing peeling of composite layer 52N can be formed.
[0062] (3) The grain area index Is is calculated by indexing the grain area ratio at the end position Xe of the composite-coated portion 51N based on the grain area ratio at the inner position Xi of the composite-coated portion 51N. The grain area index Is of the negative electrode plate 50N is 150 or more. This makes it possible to efficiently suppress peeling of the composite layer 52N.
[0063] (4) The CMC content in the composite paste 37N is 0.1 wt% or more and 1.0 wt% or more. According to the above configuration, undissolved particles 60 of CMC are present in the composite layer 52N, and the peel strength F can be efficiently increased while the undissolved particles 60 are unevenly distributed at the end position Xe of the composite coating portion 51N.
[0064] The above embodiment can be modified as follows: The above embodiment and the following modifications can be combined with each other to the extent that no technical contradiction occurs.
[0065] In the above embodiment, the CMC content in the composite paste 37N is set to 0.1 wt % or more, and 1.0 wt % or more, but the CMC content may be changed arbitrarily.
[0066] In the above embodiment, a method of adjusting the composite paste 37N containing the undissolved particles 60 of the CMC by using a CMC with a relatively low "degree of etherification" and setting the rotation speed (RPM) of the kneader low has been exemplified. However, the present invention is not limited to this, and the kneading time of the composite paste 37N may be shortened. Alternatively, the amount of the solvent in the composite paste 37N may be reduced, so that the composite paste 37N contains the undissolved particles 60 of the CMC. The "degree of etherification" of the CMC is arbitrary. Various parameters that define the kneading state of the composite paste 37N, such as the rotation speed (RPM) of the kneader, may also be changed arbitrarily.
[0067] In the above embodiment, in the coating process using the comma coater 80, the undissolved CMC particles 60 contained in the composite layer 52N are unevenly distributed at the end position Xe of the composite-coated portion 51N, more than at the inner position Xi of the composite-coated portion 51N. However, the present invention is not limited to this, and the method of unevenly distributing the undissolved CMC particles 60 contained in the composite layer 52N at the end position Xe of the composite-coated portion 51N may be changed arbitrarily. For example, a plurality of types of composite pastes 37N having different contents of the undissolved CMC particles 60 are prepared. Then, in the coating process, a method of applying different types of composite pastes 37N to the end position Xe and the inner position Xi of the composite-coated portion 51N may be used.
[0068] In the above embodiment, the "particle area ratio" of the undissolved CMC particles 60 in the microscopic image Vd obtained by binarizing the microscopic image Vd of the composite layer 52N is set to be larger at the end position Xe than at the inner position Xi of the composite-coated portion 51N. However, the present invention is not limited to this, and a state in which the end position Xe of the composite-coated portion 51N is larger than the inner position Xi of the composite-coated portion 51N and the undissolved CMC particles 60 are contained in the composite layer 52N may be specified by a method other than using such a "particle area ratio."
[0069] In the above embodiment, the "grain area", "grain area ratio", and "grain area ratio index" are calculated by acquiring a microscopic image Vd of the surface 52s of the composite layer 52N using an optical microscope. However, the present invention is not limited to this, and if the observation magnification is suitable, a microscopic image Vd other than that of an optical microscope may be used. Furthermore, the present invention is not limited to the surface 52s of the composite layer 52N, and a configuration may be used in which a microscopic image Vd of a cross section of the surface 52s is used.
[0070] In the above embodiment, the grain area index Is is 150 or more, but the grain area index Is may be less than 150. It is sufficient that the grain area index Is is at least greater than 100 (Is>100).
[0071] In the above embodiment, the position range of about 8 mm inside in the width direction from the uncoated portion 39N is set as the end position Xe of the composite-coated portion 51N. However, the present invention is not limited to this, and the specific setting of the position range of the end position Xe and the inside position Xi of the composite-coated portion 51N is arbitrary. That is, the position range in the width direction adjacent to the uncoated portion 39N where the composite layer 52N is likely to peel off may be set as the end position Xe of the composite-coated portion 51N, and any position farther away from the uncoated portion 39N than the end position Xe may be set as the inside position Xi of the composite-coated portion 51N. The position for measuring the "particle area" of the undissolved particles 60 at the inside position Xi does not necessarily have to be the center position in the width direction of the electrode sheet 35X before cutting, that is, near the set position of the slit 70 for cutting the electrode sheet 35X.
[0072] In the above embodiment, the electrode body 10 has a configuration as a wound body, but the positive and negative electrode sheets 35P, 35N stacked with the separator 5 sandwiched therebetween do not necessarily have to be wound. That is, the shape of the negative electrode plate is arbitrary. And, the secondary battery 1 to which this negative electrode plate is applied does not necessarily have to be a lithium ion secondary battery, and may be applied to other nonaqueous electrolyte secondary batteries.
[0073] The terminal shapes of the positive electrode terminal 38P and the negative electrode terminal 38N are not limited to the shapes shown in Fig. 1 and may be changed as desired. The shape of the case 20 that defines the outer shape of the secondary battery 1 is also not necessarily limited to a flat rectangular box shape and may be changed as desired, for example, to a cylindrical shape. EXAMPLES
[0074] Examples will be described below to more specifically explain the configuration and effects of the present invention, but the present invention is not limited to these examples. FIG. 17 is a table showing the results of a performance test on the negative electrode plate 50N of the secondary battery 1. The laminated structures of the negative electrode plates 50N in the "Comparative Example" and "Example 1" to "Example 3" shown in the table of FIG. 17 are all the same and similar to the above embodiment. Furthermore, the method of applying the composite paste 37N to the base material 36 is also all the same and similar to the above embodiment. The contents of the CMC and binder contained in the composite paste 37N are also all the same.
[0075] 17, "solvent amount" is the weight percent of the solvent 61 in the composite paste 37N. Furthermore, the "kneading load index" shown in the table is an index value when the "comparative example" is set to a reference value of "100", and depends on the rotation speed (RPM) of the kneading machine used to knead the composite paste 37N. The larger the value of this "kneading load index", the greater the load applied when kneading the composite paste 37N.
[0076] As shown in Fig. 17, the "Comparative Example" used CMC with an "etherification degree" of "0.89". The amount of solvent used in the composite paste 37N of this "Comparative Example" was "37.7 wt%". As for this "Comparative Example", no undissolved particles 60 of CMC could be confirmed in the composite paste 37N.
[0077] In contrast, for "Example 1" to "Example 3", a CMC with a lower degree of etherification of "0.72" was used than the CMC used in the "Comparative Example". The amount of solvent in these "Example 1" to "Example 3" is "38.1 wt%". Furthermore, the "kneading load index" is "100" for "Example 1", "90" for "Example 2", and "70" for "Example 3". As a result, the "particle area index" is "150" for "Example 1", "176" for "Example 2", and "190" for "Example 3".
[0078] That is, when comparing "Comparative Example" and "Example 1" with the same value of "Kneading Load Index", only "Example 1" with a low degree of etherification of CMC had undissolved particles 60 of CMC in the composite layer 52N. As a result, by using CMC with a relatively small value of "degree of etherification", a part of the CMC added to the composite paste 37N is likely to remain undissolved. In other words, it was confirmed that it is possible to form a composite paste 37N containing undissolved particles 60 of CMC.
[0079] In addition, when comparing "Example 1" to "Example 3" having the same value of "etherification degree", the smaller the value of the "kneading load index", the larger the value of the "particle area index". Furthermore, for these "Example 1" to "Example 3", the coating method of the composite paste 37N is all the same. In other words, the method of distributing the undissolved CMC particles 60 contained in the composite layer 52N unevenly at the end position Xe of the composite coating part 51N is common. Thus, it can be inferred that by reducing the load when kneading the composite paste 37N, it is possible to cause more undissolved CMC particles 60 to exist in the composite layer 52N.
[0080] Furthermore, when comparing "Comparative Example" with "Example 1" to "Example 3," the larger the value of the "particle area index," the higher the "peel strength index" of the composite layer 52N. Specifically, the "Comparative Example," in which undissolved CMC particles 60 were not confirmed in the composite paste 37N, had a "peel strength index" of "101." And, the "peel strength index" of "Example 1" to "Example 3," in that order, was "104," "108," and "110."
[0081] From the above results, it was confirmed that it is preferable that the end position Xe of the composite-coated portion 51N contains more undissolved CMC particles 60 in the composite layer 52N than the inner position of the composite-coated portion 51N. Furthermore, it was confirmed that the "particle area index" is an index value of the "particle area ratio" at the end position Xe of the composite-coated portion 51N based on the "particle area ratio" at the inner position Xi of the composite-coated portion 51N, and that it is more preferable that this "particle area index" is 150 or more. [Explanation of symbols]
[0082] 1…Secondary battery 35N…Electrode sheet 36N…Base material 37N…Composite paste (negative electrode composite) 39N: Uncoated area 50N…Negative electrode plate 51N…Compound coating section Xe…end position Xi…Inner position 52N…Mixture layer 60…Undissolved particles of carboxymethylcellulose (CMC)
Claims
1. a composite coating section in which the negative electrode composite coated on the substrate forms a composite layer; and an uncoated portion to which the negative electrode mixture is not applied, The negative electrode mixture contains carboxymethyl cellulose together with a negative electrode active material, A negative electrode plate containing more undissolved particles of carboxymethyl cellulose in the composite layer at an end position of the composite coated portion located at the boundary with the uncoated portion than at an inner position of the composite coated portion that is further away from the uncoated portion than the end position.
2. 2. The negative electrode plate according to claim 1, wherein the grain area ratio of the undissolved particles in the microscopic image obtained by binarizing the microscopic image of the composite layer is greater at the end position of the composite coated portion than at the inner position of the composite coated portion.
3. The particle area ratio at the end position of the composite-coated portion is indexed based on the particle area ratio at the inner position of the composite-coated portion, and the index value is defined as a particle area index.
3. The negative electrode plate according to claim 2, wherein the grain area index is 150 or more.
4. The content of the carboxymethyl cellulose in the negative electrode mixture is 2. The negative electrode plate according to claim 1, wherein the content is 0.1 wt % or more and 1.0 wt % or less.
5. A secondary battery comprising the negative electrode plate according to any one of claims 1 to 4.
Citation Information
Patent Citations
Method for manufacturing secondary battery electrode
JP2013093240A